Implementation of the Electronic Identity Card (e-KTP) Issuance Policy in Bolaang Mongondow Regency - Paputungan, Roi; Bogar, Wilson; Kairupan, Sisca B. (Technium Social Sciences Journal, 2025)
The national population administration policy that has been determined (formulation) by the government, especially the service policy for issuing Electronic Identity Cards (e-KTP) for Indonesian citizens and foreigners residing in Indonesia must be implemented properly and by the implementor. The implementor who is given the task and responsibility is the population and civil registry office. This research was conducted with the aim of analyzing and explaining the implementation of population administration order policies, especially the issuance of electronic identity cards which are focused on aspects or variables of communication, resources, disposition, and organizational structure at the Population and Civil Registration Office of Bolaang Mongondow Regency. This research uses a naturalistic (qualitative) approach. Informants who were used as data sources were determined purposively (purposive sampling) and snowball sampling. Data collection techniques were interviews, observations, and documents. Data analysis is an interactive qualitative analysis with data analysis activities, namely data reduction, data display, and conclution drawing / verification The results showed that the implementation of the Electronic Identity Card (e-KTP) issuance service policy for Indonesian citizens and foreigners residing in Indonesia as the focus and sub-focus of the research has not been implemented as it should. For this reason, it is recommended that the various variables that are the focus and sub-focus of this research as variables that determine the implementation of public policy need to be optimized both in terms of quantity and qualit.